Simulation of rock fragmentation induced by a tunnel boring machine disk cutter. (May 2016) - Li, Huiyun; Du, Erxia
A constitutive model based on the Johnson–Cook material model and the extended Drucker–Prager strength criterion was implemented in LS-DYNA to simulate the rock failure process induced by a single disk cutter of a tunnel boring machine. The normal, rolling, and side forces were determined by numerical tests. The simulation results showed that the normal and rolling forces increased with increasing penetration while the side force changed little. The normal force also increased under the conditions of confining pressures. The damage region of rock and cutting forces were also obtained by simulation of two disk cutters acting in tandem with different cutting spacings. The optimum ratio of cutter spacing to penetration depth determined from numerical modeling agrees well with that obtained by linear cutting machine tests. The average normal and rolling forces acting on the first cutter are slightly greater than those acting on the second when the cutting disk spacing is relatively small. The numerical modeling was verified to accurately capture the fragmentation of rock induced by disk cutter.